2011
DOI: 10.1038/onc.2011.1
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB-dependent cytokine secretion controls Fas expression on chemotherapy-induced premature senescent tumor cells

Abstract: Induction of a senescent phenotype in tumor cells has been linked to anticancer immune response, however, the molecular mechanisms mediating these phenomenon have not yet been determined. In this study, we present evidence that induction of premature senescence in human cancer cell lines induces Fas expression, and loss of resistance to Fas-induced apoptosis. Triggering of Fas by using the agonistic antibody CH11 or the recombinant ligand APO010, activates an apoptotic pathway responsible for cell death. Secre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 37 publications
3
48
0
Order By: Relevance
“…More importantly, it has been shown that NF-B mediates recruitment of FADD and caspase 8 to the death-inducing signaling complex to increase tumor cell sensitivity to Fasmediated apoptosis in tumor cells (28). Furthermore, NF-B was found to regulate TNF␣ and IFN-␥ expression to up-regulate Fas expression (29). These studies thus demonstrate that NF-B mediates tumor cell sensitivity to Fas-mediated apoptosis.…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…More importantly, it has been shown that NF-B mediates recruitment of FADD and caspase 8 to the death-inducing signaling complex to increase tumor cell sensitivity to Fasmediated apoptosis in tumor cells (28). Furthermore, NF-B was found to regulate TNF␣ and IFN-␥ expression to up-regulate Fas expression (29). These studies thus demonstrate that NF-B mediates tumor cell sensitivity to Fas-mediated apoptosis.…”
mentioning
confidence: 52%
“…4A). It has been shown that IFN-␥ and TNF␣, cytokines secreted by senescent tumor cells and activated immune cells, can up-regulate Fas expression (29,46,47). Indeed, IFN-␥ and TNF␣ synergistically up-regulated Fas in human colon carcinoma cells (Fig.…”
Section: Correlation Between Fas Level and Cancer Recurrence In Humanmentioning
confidence: 99%
“…In accordance with the findings from the TUNEL assay, our data showed that TNF-α was overexpressed during the early phase of WIRI whose expression could be significantly downregulated by pretreatment with APN. These data suggested that APN inhibited the activity of NF-κB (p65), consequently inhibiting the transcription of TNF-α1535.…”
Section: Discussionmentioning
confidence: 87%
“…Senescent cells secrete growth factors, cytokines, and chemokines that affect both senescent cells and neighboring cells, functioning in an autocrine and/or paracrine mode (39,40). Notably, SASP occurs in vivo in response to DNA-damaging chemotherapy (11).…”
Section: Discussionmentioning
confidence: 99%